A Numerical Model of Carbon Dioxide Concentration Measurement in a Room with an Opened Ventilation System - Wasu Timpitak; Nopparat Pochai (My University, 2021)
A vast number of patients visit the facility every day, causing a major air pollution issue that may pose a risk of exposure of respiratory infectious diseases in outpatient rooms and harm human health.TB, COVID-19, MERS, and SARS are dangerous communicable diseases that transmit from person to person through the air or aerosol in a variety of forms, such as coughing, spitting, sneezing, speaking, or through wounds.COVID-19, TB, MERS and SARS are risks and the chances of success toward lethal infection make more patients ill in the hospital.We should also be notified of the care and control of these diseases.As a result, effective air quality monitoring is needed to monitor and reduce the potential for infected air, such as carbon dioxide (CO2) concentrations.Measuring and controlling carbon dioxide in a hospital with a ventilation system where the number of patients in each room varies in time is challenging.In this research, the numerical model of carbon dioxide concentration measurement in a space with an opened ventilation system is proposed.The model sets the concentration of carbon dioxide at any point when the number of people and the rate of ventilation varies.The classical fourth-order Runge-Kutta method is employed to approximate the model solution.There are many cases of scenarios for improving air quality in the proposed simulations.In the air quality management process, the proposed model provides a balance between the number of persons allowed to stay in the room and the capacity of the air ventilation system.
Keywords: Air Quality Monitoring and Forecasting